The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3389/fnins.2011.00054
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin-Releasing Factor, Related Peptides, and Receptors in the Normal and Inflamed Gastrointestinal Tract

Abstract: Corticotrophin-releasing factor (CRF) is mainly known for its role in the stress response in the hypothalamic–pituitary–adrenal axis. However, increasing evidence has revealed that CRF receptor signaling has additional peripheral effects. For instance, activation of CRF receptors in the gastrointestinal tract influences intestinal permeability and motility. These receptors, CRF1 and CRF2, do not only bind CRF, but are also activated by urocortins. Most interestingly, CRF-related signaling also assumes an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 127 publications
(274 reference statements)
3
42
1
4
Order By: Relevance
“…Stress is able to disrupt the intestinal epithelial barrier thus increasing the penetration of luminal antigens into the lamina propria, leading to nociceptors sensitization and favoring the development of visceral hypersensitivity (Ait-Belgnaoui, et al 2005). This increase of intestinal permeability is due to an activation of peripheral CRF signaling involving both CRF2 and CRF1 (Buckinx, et al 2011) as well as mast cell activation (Santos, et al 2001). …”
Section: Intestinal Permeabilitymentioning
confidence: 99%
“…Stress is able to disrupt the intestinal epithelial barrier thus increasing the penetration of luminal antigens into the lamina propria, leading to nociceptors sensitization and favoring the development of visceral hypersensitivity (Ait-Belgnaoui, et al 2005). This increase of intestinal permeability is due to an activation of peripheral CRF signaling involving both CRF2 and CRF1 (Buckinx, et al 2011) as well as mast cell activation (Santos, et al 2001). …”
Section: Intestinal Permeabilitymentioning
confidence: 99%
“…The ligand CRF is primarily responsible for regulating and/or initiating stress responses via activation of the HPA axis (1), whereas the urocortins play a vital role in the peripheral stress response. Even though they are ubiquitously present throughout mammalian tissues, CRF, Ucn1-3 and their receptors are variably expressed in the skin (2), skeletal muscle (3), immune system (4), lung (5), heart (6), genitourinary system (7) and gastrointestinal (GI) system (8).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that activation of CRF receptors in the gastrointestinal tract affects intestinal permeability and motility [13]. Specially, CRFR1 promotes intestinal inflammation and endogenous angiogenesis, and antagonist of the receptor exhibits drastic therapeutic effect in animal models [30e32].…”
Section: Discussionmentioning
confidence: 99%
“…The peptide plays crucial roles in modulating the hypothalamic-pituitary-adrenal (HPA) axis activated by stressful stimuli, as well as behavioral, autonomic, endocrine, reproductive, cardiovascular, gastro-intestinal, metabolic and immune systemic functions, or homeostasis and viability of peripheral organs [2e5]. Moreover, CRF effects have also been found in tumorgenesis [6,7], mood disorders [8], neuroplasticity [9,10], skin stress response system [11], inflammation [12,13], addiction [14e16] and Alzheimer's disease [17]. CRF exerts its biological function via binding to its receptors (CRFR).…”
Section: Introductionmentioning
confidence: 99%